Pengaruh Employee Engagement Terhadap Kinerja Karyawan Direktorat Sistem Informasi dan Transformasi Digital Institut Pertanian Bogor (Jurnal Manajemen dan Organisasi, 2020)
Employees who are engaged will give the best performance and do things related to the job optimally in order to achieve the goals of the institution. This study aims to analyze the influence of employee engagement on the performance of employees of the Directorate of Information Systems and Digital Transformation (DSITD) of IPB University. The research method used is quantitative research method, using descriptive statistik analysis and multiple linear regression analysis. The results of the study can be concluded that the state of employee engagement and employee performance in DSITD IPB is in good category. Partially, absorption elements have been found to effect the employee performance. However, together with vigor and dedication, absorption element have an effect of 67,5 percent on employee performance, meaning that of all variables that can affect employee performance, employee engagement only affects 67,5 percent.